2011
DOI: 10.1021/la2014754
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Bilayer Templated Gold Nanoparticles Nanoring Formation Using Zirconium Ion Coordination Chemistry

Abstract: We used positively charged lipids to prepare lipid bilayer assemblies (LBAs) upon which we assembled negatively charged gold nanoparticles (AuNPs). Treatment of the assembly with zirconium chloride resulted in the formation of nanorings of the diameters inversely related to the zirconium ion concentration. The nanorings were attributed to the zirconium ion coordinated AuNPs formed during the lipid bilayer budding process promoted by the acid effect of zirconium chloride. Nanoring organization was also dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 39 publications
2
12
0
Order By: Relevance
“…Perforation of lipid membranes by LPS was suggested by previous indirect evidence of electrical resistance of lipid membranes stretched across an aperture where treatment with LPS (110-720 mg/mL) led to a decreased resistance and eventual collapse (60). Holes and other lesions can be formed in lipid bilayers by various small molecules, including pore-forming protein toxins (61), highly charged synthetic nanoparticles (62)(63)(64)(65)(66), and polycationic polymers (67)(68)(69)(70)(71). Hole formation in each case is dependent upon the specific interactions between the membrane and the disruptive molecule of interest.…”
Section: Membrane Effects Induced By Lps-na Dmentioning
confidence: 99%
“…Perforation of lipid membranes by LPS was suggested by previous indirect evidence of electrical resistance of lipid membranes stretched across an aperture where treatment with LPS (110-720 mg/mL) led to a decreased resistance and eventual collapse (60). Holes and other lesions can be formed in lipid bilayers by various small molecules, including pore-forming protein toxins (61), highly charged synthetic nanoparticles (62)(63)(64)(65)(66), and polycationic polymers (67)(68)(69)(70)(71). Hole formation in each case is dependent upon the specific interactions between the membrane and the disruptive molecule of interest.…”
Section: Membrane Effects Induced By Lps-na Dmentioning
confidence: 99%
“…Also, high‐resolution AFM images demonstrated that membrane defects were also formed inside the nanorings 58. The nature of the reorganization was investigated and it could be explained by a mechanism involving both metal coordination and the previously described pH effects of membrane reorganization and disruption 26, 58. In brief, the Zr metal allowed for coordination of COOH groups on the Au NPs.…”
Section: Lipid Membrane Organization and Dynamics Via Afmmentioning
confidence: 91%
“…The observation was the same for both positively and negatively charged particles, indicating that all particle collisions are elastic in the absence of electrostatic attractions and with substrate support. The other interactions, such as hydrogen bonding, are not strong enough to bring the particle close enough to the LBA or eliminate the hydration layers of water around the hydrophilic lipid headgroups 57–59…”
Section: Lipid Membrane Organization and Dynamics Via Afmmentioning
confidence: 99%
See 2 more Smart Citations